theorem znegeqcom (a b: nat): $ -uZ a = b <-> -uZ b = a $;
Step | Hyp | Ref | Expression |
1 |
|
|
(-uZ a = b <-> a +Z b = 0) -> (-uZ b = a <-> a +Z b = 0) -> (-uZ a = b <-> -uZ b = a) |
2 |
|
|
|
3 |
|
|
(-uZ b = a <-> a +Z b = 0) -> (-uZ a = b <-> -uZ b = a) |
4 |
|
|
(-uZ b = a <-> b +Z a = 0) -> (a +Z b = 0 <-> b +Z a = 0) -> (-uZ b = a <-> a +Z b = 0) |
5 |
|
|
|
6 |
|
|
(a +Z b = 0 <-> b +Z a = 0) -> (-uZ b = a <-> a +Z b = 0) |
7 |
|
|
a +Z b = b +Z a -> (a +Z b = 0 <-> b +Z a = 0) |
8 |
|
|
|
9 |
|
|
a +Z b = 0 <-> b +Z a = 0 |
10 |
|
|
|
11 |
|
|
|
Axiom use
axs_prop_calc (+5)
(ax_1,
ax_2,
ax_3,
ax_mp,
itru),
axs_pred_calc (+8)
(ax_gen,
ax_4,
ax_5,
ax_6,
ax_7,
ax_10,
ax_11,
ax_12),
axs_set (+2)
(elab,
ax_8),
axs_the (+2)
(theid,
the0),
axs_peano (+9)
(peano1,
peano2,
peano5,
addeq,
muleq,
add0,
addS,
mul0,
mulS)